1983
DOI: 10.1364/ol.8.000491
|View full text |Cite
|
Sign up to set email alerts
|

Maximum statistical increase of optical absorption in textured semiconductor films

Abstract: Complete statistical randomization of the direction of propagation of light trapped in semiconductor films can result in a large absorption enhancement. We have employed a calorimetric technique, photothermal deflection spectroscopy, to monitor the absorption of alpha-SiH(x) films textured by the natural lithography process. The observed enhancement factors, as high as 11.5, are consistent with full internal phase-space randomization of the incoming light.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(50 citation statements)
references
References 7 publications
(11 reference statements)
2
48
0
Order By: Relevance
“…A Lambertian angular distribution of light is likely achieved after several internal reflections, but this approximation is crude for the first few bounces and is better suited to the analysis of thin-film devices with nanoscale textures. 9,47 We chose instead to employ a ray tracer to track rays inside the cell, obviating the need to assume an angular distribution function at all. For each internal reflection, the tracer knows the angle of incidence and can thus adopt the appropriate results from Fig.…”
Section: Simulation and Measurement Of Total Reflectancementioning
confidence: 99%
“…A Lambertian angular distribution of light is likely achieved after several internal reflections, but this approximation is crude for the first few bounces and is better suited to the analysis of thin-film devices with nanoscale textures. 9,47 We chose instead to employ a ray tracer to track rays inside the cell, obviating the need to assume an angular distribution function at all. For each internal reflection, the tracer knows the angle of incidence and can thus adopt the appropriate results from Fig.…”
Section: Simulation and Measurement Of Total Reflectancementioning
confidence: 99%
“…Here, we use the well-known conic problem of scattered fields from a metallic sphere in a vacuum space (shown in Ref [39]) to validate our models for MNPs. If an electric field of a uniform plane wave is polarized in the x direction, and is traveling along the z-axis, then the monostatic radar cross section can be expressed by (1) where r, E s , E i , λ, β, a, and H (2) are represent the range, scattered electric field, incident electric field, wavelength, wave propagation constant, radius of the metallic sphere, and spherical Hankel function, respectively. A plot of equation 1 as a function of the radius of the sphere is shown in Figure 6.…”
Section: Electromagnetic Field Analysis Of Mnpsmentioning
confidence: 99%
“…Fortunately, there are different methods to achieve such enhancement. For instance, applying a randomly textured layer inside the device is a standard approach to gain more effective scattered rays inside the device [2][3][4][5]. Additionally, introducing a periodic structure as a reflector to enable the increase of light path inside the absorber [6][7][8]; thus enhancing light absorption.…”
Section: Introductionmentioning
confidence: 99%
“…Deckman et al [57] were the first who experimentally demonstrated absorption enhancement factors of up to 12. The same authors also showed that the achievements were directly translated into 25% higher short-circuit currents [58], though extremely thick a-Si:H absorber layers around 1 µm were used in both studies.…”
Section: Fig 213mentioning
confidence: 99%